Cervical cancer - is there anything to worry about? Research on knowledge and awareness of cervical cancer among Poles - Dominika Mańdziuk; Klaudia Kołodziej; Michał Żuchowski; Patrycja Niewinna; Przemysław Zaroda; Paweł Dąda; Paweł Pawlik; Wojciech Kołodziej; Jakub Wawrzkowicz; Monika Korga (Kazimierz Wielki University, 2024)
Cervical cancer poses a global health challenge, being one of the most common cancers of the reproductive organs and a leading cause of morbidity and mortality worldwide. The disease, resulting from infection with the human papillomavirus (HPV), tends to develop in advanced stages, significantly complicating effective treatment. Despite advancements in medicine, diagnostics, and therapy, cervical cancer remains a serious public health threat. Periodic surveillance through screening has significantly reduced the incidence of cervical cancer; however, in Poland, there is a notable gap between potentially available preventive measures and their actual utilization by the population. It has been observed that only around 20% of Polish women participate in screening programs, contributing to Poland having one of the highest rates of incidence and mortality from this type of cancer in Europe. This leads to the conclusion that cervical cancer constitutes an unresolved oncological and epidemiological problem in Poland. In the context of these challenges, a crucial aspect is understanding the level of public knowledge about cervical cancer, its risk factors, and available preventive measures. This study focuses on evaluating the societal knowledge regarding the risk factors of cervical cancer, identifying existing gaps, and suggesting potential areas for educational interventions.